PENGGUNAAN KOSAKATA DAN TATABAHASA DALAM BERITA “VIRAL SUAMI SELINGKUH DENGAN IBU MERTUA, DIGEREBEK WARGA HINGGA ISTRI ALAMI TRAUMA” (ANALISIS WACANA KRITIS ROGER FOWLER) - Septian Gazali Rukmana; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to describe the analysis of critical discourse in online news from Kompas.com December 2023 edition based on Roger Fowler's Theory. The data source for this research is a viral news article from Kompas.com online news with the title "Viral: Husband Cheats with Mother-in-Law, Caught Red-Handed by Residents, Wife Traumatized." The method used in this study is descriptive with qualitative data analysis. Based on the analysis conducted by the researcher using Roger Fowler's theory, which determines the selection of vocabulary and grammar, it can be concluded that there are quotations with vocabulary for classification, quotations with vocabulary for discursive struggle, and quotations with vocabulary for marginalization. There are news texts that use active-passive grammar, news texts with passive-passive grammar, and news texts that use nominalization grammar. This research can be beneficial for learning and can provide insights and knowledge for future researchers. Keywords: critical discourse analysis, Roger Fowler's theory.